Potential of Zanthoxylum leprieurii as a source of active compounds against drug resistant Mycobacterium tuberculosis - Bunalema, Lydia (BMC Complement Altern Med, 2017)
BACKGROUND: Tuberculosis (TB) is still a global health problem mainly due to development of resistance and co-infection with the Human immune Virus (HIV). Treatment of multi and extensively drug resistant TB requires use of second line drugs which are less efficacious, expensive and very toxic. This has necessitated a need to search for new treatment regimens especially from medicinal plants. Zanthoxylum leprieurii, a plant species from Rutaceae is used locally in the treatment of tuberculosis in Uganda. The aim of the study was to isolate, identify and characterize bio active compounds from Z. leprieurii stem bark with antimycobacterial activity. METHODS: Crude extracts, fractions and compounds from air dried stem bark of Z. leprieurii were tested against pan sensitive (H37rv), isoniazid resistant (TMC 301) and rifampicin resistant (TMC 331) strains of M. tuberculosis using micro plate alamar blue assay. Isolation of active compounds was done by using column chromatography and thin layer chromatography. They were analysed using nuclear magnetic resonance spectroscopy and mass spectroscopy. RESULTS: The methanol extract had minimum inhibitory concentrations (MIC) of 47.5, 75.3 and 125.0 μg/ml on the pan sensitive strain, rifampicin resistant and isozianid resistant strains of M. tuberculosis respectively. The chloroform extract had MIC values of 260 μg/ml agnaist the pan sensitive strain and 156 μg/ml on the rifampicin resistant strain. Of the sixteen fractions from the methanol extract, fraction Za(4) (MIC = 6.3 μg/mL, 23.0 μg/mL, 11.7 μg/mL) and Za(6) (MIC = 11.7 μg/mL 31.2 μg/ml, 31.2 μg/ml) were the most active. Three acridone alkaloids; hydroxy-1, 3-dimethoxy-10-methyl-9-acridone (1), 1-hydroxy-3-methoxy-10-methyl-9-acridone (2) and 3-hydroxy-1, 5, 6-trimethoxy-9-acridone (3) were isolated from Za(4) and Za(6). The MIC of compound 3 was found to be 5.1 μg/ml, 4.5 μg/ml and 3.9 μg/ml on H37rv, TMC 331 and TMC 301 while that of 1 was found to be 1.5 μg/ml, 8.3 μg/ml and 3.5 μg/ml respectively. CONCLUSION: The results of this study suggest that Z. leprieurii is active on resistant strains of M. tuberculosis and could be a potential source of new leads against resistant tuberculosis. It also verifies the local use of the plant in treatment of tuberculosis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12906-017-1602-x) contains supplementary material, which is available to authorized users.